Designing a quantitative PCR assay for fetal RhD genotyping from maternal plasma derived cell-free fetal DNA - Parviainen, Suvi (My University, 2022)
Hemolytic disease of the fetus and newborn (HDFN) is typically caused by maternal alloimmunization against antigens of RhD positive red blood cells. During pregnancy, these anti-RhD antibodies can induce the destruction of fetal RhD positive red blood cells and lead to HDFN. Maternal alloimmunization can be prevented with antenatal and postnatal anti-D prophylaxis treatment, which is often routinely performed for all RhD negative mothers. However, fetal RhD genotyping allows anti-D prophylaxis to be targeted only for women carrying RhD positive fetus. Therefore, unnecessary anti-D prophylaxis treatments can be avoided. The aim of the study was to develop a multiplexed, quantitative PCR (qPCR) assay for fetal RhD genotyping using maternal plasma derived cell-free fetal DNA (cffDNA) as sample material. The fetal RhD genotyping assay was designed for simultaneous detection of RHD gene exons 5, 7 and 10, in addition to an internal control gene. The assay was confirmed to be compatible with cfDNA samples extracted with PerkinElmer Vanadis Extract® system. The assay was able to distinguish RhD positive and negative cfDNA samples and showed similar performance with both liquid and dried qPCR chemistry. The presence of fetal DNA in the maternal cfDNA samples was demonstrated by amplification of male-specific sex-determining region Y (SRY) gene. Dried qPCR chemistry enables a simple and time-saving workflow, which can be easily combined with other prenatal cffDNA screening. Further clinical testing is required to determine clinical sensitivity and specificity.
Keywords: Hemolytic disease of the fetus and newborn, RhD, cell-free fetal DNA, quantitative polymerase chain reaction